2018
DOI: 10.1016/j.sedgeo.2017.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Are inundation limit and maximum extent of sand useful for differentiating tsunamis and storms? An example from sediment transport simulations on the Sendai Plain, Japan

Abstract: We examined the quantitative difference in the distribution of tsunami and storm deposits based on numerical simulations of inundation and sediment transport due to tsunami and storm events on the Sendai Plain, Japan. The calculated distance from the shoreline inundated by the 2011 Tohoku-oki tsunami was smaller than that inundated by storm surges from hypothetical typhoon events. Previous studies have assumed that deposits observed farther inland than the possible inundation limit of storm waves and storm sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 41 publications
3
35
0
Order By: Relevance
“…Generally, scientists assume that wind wave-driven runup cannot reach those limits (e.g., Cox et al, 2018). Furthermore, geologists characterize deposits based on the hydrodynamic differences between tsunamis and storm, which create distinctive sedimentary patterns (Mamo et al, 2009;Switzer & Jones, 2008;Tuttle et al, 2004;Watanabe et al, 2017Watanabe et al, , 2018. Nevertheless, recent observations of apparent infragravity (IG) dominated flooding during storm and swell events appear very tsunami-like due to the generated extreme runup (Roeber & Bricker, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, scientists assume that wind wave-driven runup cannot reach those limits (e.g., Cox et al, 2018). Furthermore, geologists characterize deposits based on the hydrodynamic differences between tsunamis and storm, which create distinctive sedimentary patterns (Mamo et al, 2009;Switzer & Jones, 2008;Tuttle et al, 2004;Watanabe et al, 2017Watanabe et al, , 2018. Nevertheless, recent observations of apparent infragravity (IG) dominated flooding during storm and swell events appear very tsunami-like due to the generated extreme runup (Roeber & Bricker, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This is because, in some cases, it is possible that such deposits might also be explained by unusually large‐scale storm surges (e.g. Morton et al ., ; Pilarczyk et al ., ; Soria et al ., ; Watanabe et al ., , ). In this study, it is also difficult to determine whether PL‐b was formed by a past tsunami or storm surge based solely on its distribution and sedimentological characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…However, Watanabe et al . () examined the quantitative difference in the distribution of tsunami and storm deposits based on numerical simulations of inundation and sediment transport due to tsunami and storm events on the Sendai Plain (Japan) and concluded that the calculated distance from the shoreline inundated by the 2011 Tohoku‐oki tsunami was smaller than that inundated by storm surges from hypothetical typhoon events. Watanabe et al .…”
Section: Discrimination Of Tsunami Depositsmentioning
confidence: 99%
“…Watanabe et al . () suggested that in the case of gently sloping coasts the inundation limit of storm surges may be further inland than that of tsunamis. These authors suggested the use of the total volume of sediment deposited to differentiate tsunami and storm deposits.…”
Section: Discrimination Of Tsunami Depositsmentioning
confidence: 99%
See 1 more Smart Citation